Le temps donné aux tableaux Une enquête au musée Granet, augmentée d'études sur la réception de la peinture et de la musique - Passeron, Jean-Claude (Bibliothèque idéale des sciences sociales, 2019)
The sociology of the reception of artistic works attempts to exploit the fact - often mentioned in theoretical terms but rarely explored empirically - that works only exist and last because of the interpretative activity of their viewers: readers and spectators are always present as third parties placed between the meaning which the artist gave to their work and that which is attributed by those whose receive it. In order to apprehend such acts of reception a team of researchers lead by Jean-Claude Passeron and Emmanuel Pedler in 1987 followed visitors to the Musée Granet in Aix-en Provence chronometer in hand. Their aim was to uncover the social factors which underlie the 'time given to the paintings'. Since its publication in 1991 the present work, which gave an account of the original study, has been cited rather more often that it has been read. Now reedited in the Bibliothèque idéale des sciences sociales it has been augmented by several important articles in which the authors of the original study pursued their analysis of the reception of artistic works, both in the fields of both pictures and music. In an attempt to describe and measure precisely the 'pacts' of reception that are created between the works of art and their public, the ensemble proposes a sociology centred on the fate of singular works which is different from the sociology of cultural consumption which currently dominates sociological surveys of culture. As an attempt to identify the semic acts of aesthetic experience by identifying them with objective indicators it positins itself firmly within the sociology of inquiry. In addition to this collection of texts, a long interview with Jean-Claude Passeron and Emmanuel Pedler allows readers to discover the general perspective in which this exemplary survey was carried out and how it influenced their subsequent work. Finally, and perhaps the post original aspect of the reedition, it provides readers with the original data of the survey, thus allowing them to prolong the authors' analyses and to explore further the avenues opened by an approach whose fertility heuristic is as pertinent as it ever was.